(untitled) (Coordinates of Public Administration, 2026)
The article analyzes the status and mechanisms of implementing the barrier-free policy in Ukraine at the regional and local levels; special attention is paid to highlighting the disparities between regional centers and rural territorial communities; It was found that despite the adoption of the National Strategy for Creating a Barrier-Free Space by 2030, there is a significant gap in Ukraine between declarative goals at the central level and their practical implementation in the regions and municipalities, especially in the context of decentralization, where responsibility has been transferred to territorial communities; It has been revealed that a transformation of the social paradigm is taking place in Ukraine, where accessibility ceases to be just a matter of the availability of ramps and becomes a philosophy of dignity and equal rights; it has been proven that without equalization of potentials, we risk getting a country of «deserts» around several flourishing megacities; It is shown that in the context of the full-scale aggression of the Russian Federation and the growing number of veterans and civilians with injuries, the issue of physical, sensory and digital accessibility is becoming critical for national security and social cohesion; the European experience of creating an inclusive environment is considered and recommendations are offered for local governments; that the main indicator of the success of decentralization should not be the size of the community budget, but the level of autonomy of its most vulnerable residents; it was found that rural accessibility is not a luxury, but a tool for returning human capital to the community, accessibility in the context of decentralization cannot be implemented exclusively «top-down», since this process requires a combination of state strategy and local initiative.